Does Midcarpal Joint Structure Affect Development of Arthritis in the Wrist - Tesoriero, Paul; Becker, Jacob; Passano, Brandon; Huang, Shengnan; Petchprapa, Catherine; Wollstein, Ronit (Journal of Wrist Surgery, 2022)
Background Degenerative wrist arthritis develops in specific patterns because of forces acting on existing structural configurations. The most common pattern of wrist osteoarthritis is scapholunate advanced collapse (SLAC). Other patterns include isolated scaphotrapezial trapezoid (STT) joint and isolated midcarpal or radiolunate joint arthritis. One predictor of degeneration pattern is the structure of the wrist.Questions/Purposes Our purpose was to evaluate the relationship between midcarpal joint structure and the pattern of degenerative arthritis. We hypothesized that a wrist type 2 will preferentially develop SLAC degeneration.Patients and Methods We retrospectively evaluated 195 degenerative wrist radiographs. Radiographs were reviewed for lunate/wrist type, degeneration pattern, ulnar variance, radial and volar tilt, inclination, carpal height, scapholunate angle, gap, and presence of thumb carpometacarpal (CMC) joint, STT joint, and midcarpal joint arthritis.Results We had 158 radiographs with SLAC degeneration and 37 with atypical patterns, 154 type 2 and 41 type 1 wrists. There was a significant correlation between wrist type and the pattern of wrist degeneration (p = 0.02). SLAC degeneration developed in wrists with type 2 lunate while isolated midcarpal arthritis was associated with type 1 wrist. Isolated midcarpal joint arthritis was associated with STT arthritis, p < 0.01. Radial height, inclination, volar tilt, and ulnar variance, and scapholunate gap and angle were not associated with wrist type. Ulnar variance was associated with thumb CMC and STT joint arthritis while radial height was associated with isolated midcarpal joint arthritis.Conclusion This study found significant relationships between midcarpal joint structure and pattern of degeneration. This contributes to understanding the development of degeneration and can aid in future prevention of arthritis.Level of Evidence This is a Level IV, diagnostic study.
Keywords: arthritis; lunate type; midcarpal joint; SLAC; wrist